A fresh look at microplastics and other particles in the tropical coastal ecosystems of Tamandaré, Brazil. (July 2021) - Lins-Silva, Nathália; Marcolin, Catarina R.; Kessler, Felipe; Schwamborn, Ralf
Abstract: Plankton organisms, biogenic particles, inorganic mineral particles, and microplastics are the four main components of particulate organic matter in aquatic ecosystems. We propose a new index, the Relative Microplastics Concentration (RMC, in %), considering that microplastics are more deleterious when food is scarce. A total of 112 plankton net samples were collected in estuarine, coastal and shelf environments of Tamandaré, Brazil. Particles were identified by image analysis (ZooScan) and FTIR. Higher concentrations of total microplastics, PP (Polypropylene) and PE (Polyethylene) in the estuary indicate an oceanward decreasing gradient from terrestrial sources. Higher concentrations of nylon fibres were found offshore. Yet, RMC indicated that the Bay had the most severely impacted ecosystems (RMC: 2.4% in the estuary, 5.1% in the Bay, and 2.0% on the shelf), for total microplastics and PP & PE. Shelf ecosystems were most severely impacted with nylon fibres. RMC analysis provided a new perspective into the impact of microplastics on tropical coastal food webs. Highlights: Higher concentrations of total microplastics and PP&PE (Polypropylene & Polyethylene) were found in the Estuary. Nylon fibers were more abundant at mid-shelf than in the Bay area. Maximum relative concentration of nylon fibers was found on the Shelf. We propose a new index, the Relative Microplastics Concentration (RMC, in %). Relative Microplastics Concentration (RMC) impact was maximum in the coral-reef lined Bay.